Therapie mit Dabigatran - Spannagl, M.; Bauersachs, R.; Debus, E. S.; Gawaz, M.; Gerlach, H.; Haas, S.; Hach-Wunderle, V.; Lindhoff-Last, E.; Riess, H.; Schellong, S.; Schinzel, H.; Bode, C. (Hämostaseologie, 2012)
Summary Dabigatran, an oral, reversible direct factor IIa inhibitor, is approved in Europe for stroke prevention in atrial fibrillation and for the prevention of venous thromboembolism after elective hip and knee replacement. In contrast to vitamin K antagonists, a routine coagulation monitoring during the treatment with dabigatran etexilate is not necessary. However, in specific clinical situations such as invasive emergency procedures or serious haemorrhage, the actual anticoagulant status of dabigatran may be of importance for the treating clinician and can be assessed by clotting tests (aPTT, TT, ECT). The diluted thrombin time test (Hemoclot®), which is specifically calibrated for dabigatran, is useful for quantitative determination of the dabigatran serum concentration. In general, discontinuation of dabigatran etexilate 24 hours before standard elective surgery is sufficient to normalise the bleeding risk in patients with normal renal function. In patients with renal impairment and/or in the case of a high bleeding risk procedure the recommended duration of discontinuation is prolonged. If a bleeding episode occurs in a patient on dabigatran, further treatment should be based on the severity and localisation of the bleeding. A distinct feature of dabigatran is the possibility of effectively removing dabigatran from the circulation by haemodialysis. Recommendation: In the case of clinically minor bleedings, a delay in the administration of the next dabigatran etexilate dose is recommended. The length of the delay is based on the patient’s individual thromboembolic risk. In minor bleedings the use of prothrombin complex concentrates is not indicated. In the case of moderate or major bleedings the main focus should be on stabilising the circulation by using fluids and blood products and, if a lesion can be identified, the local treatment thereof. If time and infrastructure is available, dialysis offers an effective and fast option to remove dabigatran out of the circulation. In the incidence of severe and life threatening bleedings, an additional, more complex haemostasis management is required. Besides haemodynamic stabilisation of the circulation, administration of prothrombin complex concentrates should not be delayed. It has to be kept in mind that standard laboratory coagulation parameters may not accurately reflect the effect of prothrombin complex concentrates in patients on dabigatran. Hence the effect of the prothrombin complex concentrate should be monitored clinically and adjusted by means of onset of coagulation in vivo.
Keywords: Dabigatran; Dabigatran etexilate; atrial fibrillation; stroke prevention; thrombosis prophylaxis; perioperative management; activated partial thromboplastin time; aPPT; ecarin clotting time; ECT; thrombin time; TT; diluted thrombin time; Hemoclot®